The practicality of popular scientific books on Myrtaceae ethnobotany found in Forest Areas with Special Purposes (KHDTK) ULM - Luthfia Noorannisa; Yudi Firmanul Arifin; Dharmono Dharmono (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
This development research has the aim of describing the practicality of the popular scientific book on ethnobotany Myrtaceae Forest Areas with Special Purposes (KHDTK) ULM which is an education and training forest under the institution of Lambung Mangkurat University. This popular scientific book (BIP) was developed through Tessmer's Formative Evaluation, while the stages carried out were conducting a self-evaluation, followed by expert validation, student readability test (one-to-one evaluation), Small Group Test, and Field Test. The results of the practicality test of the contents of the one-to-one evaluation get an average value of 95.51% with very good criteria. Based on the results of the implementation test, the expectation was to get a percentage of 88.89% and the actual 92.22% was expected with very good criteria. the students' s response was expected to get a percentage of 96.80% and the actual 97.40% with very practical criteria. Based on the results of the research developed, it can be stated that the Popular Scientific Books (BIP) developed can be used in improving students' critical thinking skills because the scientific books developed have very practical criteria.Abstrak Penelitian pengembangan ini memiliki tujuan mendeskripsikan kepraktisan buku ilmiah populer etnobotani Myrtaceae Kawasan Hutan Dengan Tujuan Khusus (KHDTK) ULM yang merupakan hutan pendidikan dan pelatihan yang ada di bawah lembaga Universitas Lambung Mangkurat. Buku ilmiah populer (BIP) ini dikembangkan melalui Evaluasi Formatif Tessmer, adapun tahapan yang dilakukan yaitu melakukan evaluasi diri, dilanjutkan dengan validasi ahli, Uji keterbacaan mahasiswa (one-to-one evaluation), Uji Small Group, dan uji Field Test. Hasil penelitian uji kepraktisan isi pada uji one-to-one evaluation mendapatkan nilai rata-rata 95,51% dengan kriteria sangat baik. Berdasarkan hasil uji keterlaksanaan harapan mendapatkan presentase 88,89% dan aktual 92,22% harapan dengan kriteria sangat baik. Respon mahasiswa harapan mendapatkan presentase 96,80% dan aktual 97,40% dengan kriteria sangat praktis. Berdasarkan hasil penelitian yang dikembangkan maka dapat dinyatakan bahwa Buku Ilmiah Populer (BIP) yang dikembangkan dapat digunakan dalam meningkatkan keterampilan berpikir kritis mahasiswa karena buku ilmiah yang dikembangkan mendapatkan kriteria sangat praktis.